Health-related quality of life and emotional problems in children surviving brain tumor treatment: A descriptive study of 2 cohorts. (3rd July 2016) - Dessens, Arianne B.; van Herwerden, Michael C.; Aarsen, Femke K.; Birnie, Erwin; Catsman-Berrevoets, Coriene E.
ABSTRACT: The survival of childhood brain tumors has improved in the past 30 years, but acquired brain injury due to damage caused by tumor invasion and side effects of different treatment modalities frequently occurs. This study focused on residual impairments, health-related quality of life (HRQoL), and emotional and behavioral problems in 2 cohorts of survivors diagnosed and treated for various types of brain tumors. Survivors in the 2004 cohort visited the Erasmus Medical Centre for standardized follow-up between 2003 and 2004, and in the 2014 cohort, between 2012 and 2014. Data of neurologically impairments of all children were extracted from medical records. Parents and survivors filled out questionnaires on quality of life and emotional and behavioral problems. In both cohorts, approximately 55% of the survivors displayed neurologic impairments. In comparison with the healthy reference group, a reduced parent-reported quality of life was found on the Motor, Cognition, and Autonomy (Cohort 2004) scales. Comparison between the cohorts showed that parents in the 2004 cohort reported a higher HRQoL on the Motor and Cognitive functioning scales. In the 2014 cohort, children reported less negative emotions than healthy children. No increase in emotional or behavioral problems were reported by children in both cohorts, whereas parents reported problems in social functioning and isolation related to a delay in emotional development. Children surviving brain tumor treatment have a reduced quality of life. The authors therefore recommend regular screening of HRQoL and emotional and behavioral problems and referral to specific aftercare.